2001
DOI: 10.1046/j.1439-0272.2001.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-cell volumetric measurements as parameters in bull semen function evaluation: correlation with nonreturn rate

Abstract: Sperm-cell volume, measured electronically by cell counter, is a parameter providing information about the state and integrity of the plasma membrane by determining cell osmotic reactivity (swelling level). Electronic volume measurement is a modification of the hypo-osmotic swelling test, based on the increase in sperm volume in response to hypo-osmotic stress. In this study the volumetric method was applied to bull ejaculates, and the relationships of volumetric parameters, osmolality of seminal plasma, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…Inhibition of volume regulation in human ejaculated spermatozoa leads to failure in the penetration of and migration through surrogate cervical mucus, because of reduced swimming velocity of the swollen cells [22]. Sperm volumetric responses have also been shown to be correlated to the fertility of cattle [23]. In man, sperm volume regulation capacity is lower in infertile patients than in fertile men [24] or semen donors [25].…”
Section: Physiological Osmotic Challenges To Spermatozoa and Cell Volmentioning
confidence: 99%
“…Inhibition of volume regulation in human ejaculated spermatozoa leads to failure in the penetration of and migration through surrogate cervical mucus, because of reduced swimming velocity of the swollen cells [22]. Sperm volumetric responses have also been shown to be correlated to the fertility of cattle [23]. In man, sperm volume regulation capacity is lower in infertile patients than in fertile men [24] or semen donors [25].…”
Section: Physiological Osmotic Challenges To Spermatozoa and Cell Volmentioning
confidence: 99%
“…Several assays have been used to evaluate plasma membrane integrity of bovine sperm based on either permeability of the membrane to different dyes (supravital stain) or the ability of sperm cell to respond to stress (hypo-osmotic swelling test, HOST) (Petrunkina et al, 2001). Although both tests are subjective, they evaluate different aspects of plasma membrane integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Such volume regulation is one of the major sperm properties relevant to environmental adaptation and functional integrity. In human, bovine, porcine, canine, and murine sperm, it has been shown that volume regulation occurs by means potassium and chloride ion transport and coupled water efflux (77)(78)(79)(80)(81). Using quinine-and 5-nitro-2-(3-phenylpropylamino)-benzoic acid-sensitive channels, respectively, the ions leave in tandem to maintain electroneutrality.…”
Section: Volume Regulationmentioning
confidence: 99%
“…In cattle, spermatozoa with superior volume regulation have been shown to be selected for preferential binding by the female genital tract, therefore having a higher chance to fertilize than sperm with poor volume regulation (85). Moreover, in cattle, individuals whose sperm show superior volume regulation demonstrate higher fertility performance as monitored by nonreturn rates, whereas poor volume regulation has been noted in sperm from subfertile boars and bulls (77,80,85). One should note also that for industrial breeding, it is important that ejaculated sperm maintain good volume regulatory ability, because they will be exposed to stress during liquid preservation and storage and particularly during cryopreservation.…”
Section: Volume Regulationmentioning
confidence: 99%